2020
DOI: 10.1101/2020.01.10.902668
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The rifampicin-inactivating mono-ADP-ribosyl transferase ofMycobacterium smegmatissignificantly influences reactive oxygen species levels in the actively growing cells

Abstract: A classic example of antibiotic inactivating function in bacteria is the Mycobacterium smegmatis (Msm) encoded rifampicin-inactivating mono-ADP-ribosyl transferase (arr). Since its probable biological role has been proposed to be in DNA damage response, which is inflicted by reactive oxygen species (ROS), in the present study, we examined whether Msm Arr influences ROS levels. For this purpose, the levels of the ROS, hydroxyl radical and superoxide, were determined in the mid-log phase (MLP) cells of Msm arr k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 68 publications
7
11
0
Order By: Relevance
“…Precursors lethal concentrations of rifampicin/moxifloxacin, as demonstrated by us in the present study and earlier (9)(10)(11). It implied that these subpopulations contained rifampicintolerant cells, as defined (16), classical persisters, as termed (4,5), and several other phenotypic subpopulations that might survive using several other mechanisms (2, 7).…”
Section: Merits Of Multinucleated/septated/constricted Division Of Ansupporting
confidence: 73%
See 3 more Smart Citations
“…Precursors lethal concentrations of rifampicin/moxifloxacin, as demonstrated by us in the present study and earlier (9)(10)(11). It implied that these subpopulations contained rifampicintolerant cells, as defined (16), classical persisters, as termed (4,5), and several other phenotypic subpopulations that might survive using several other mechanisms (2, 7).…”
Section: Merits Of Multinucleated/septated/constricted Division Of Ansupporting
confidence: 73%
“…We used 10ϫ MBC rifampicin, in addition to 1ϫ MBC rifampicin, for exposure because M. smegmatis, unlike M. tuberculosis, has ADP-ribosyl transferase (Arr) that inactivates rifampicin (17). We have confirmed that 10ϫ MBC rifampicin inflicts lethality on M. smegmatis (10 8 cells/ml) despite having Arr (11). Further, 10 6 cells/ml were used for exposure to rifampicin to preempt the emergence of natural rifampicin resisters at ϳ10 Ϫ8 frequency (11,18).…”
Section: Resultsmentioning
confidence: 76%
See 2 more Smart Citations
“…Hydroxyl radical being a mutagen without nucleotide sequence specificity (Imlay et al, 1988; Sakai et al, 2006), we examined the benefits of its differential levels between the SCF and the NCF cells in terms of resister generation frequency against two anti-tuberculosis antibiotics, rifampicin and moxifloxacin, which have completely different targets of action. For this purpose, the freshly fractionated Msm SCF and NCF cells were entirely plated on Middlebrook 7H10 agar containing rifampicin (125 μg/ml; 3× MBC; Swaminath, 2017) or moxifloxacin (0.5 μg/ml; 5× MBC; Swaminath, 2017). The colonies from the rifampicin and moxifloxacin plates showed mutations in the rifampicin resistance determining region (RRDR) and quinolone resistance determining region (QRDR) for rifampicin and moxifloxacin resistance, respectively (Supplementary Figures S3, S4, respectively; Takiff et al, 1994; Yue et al, 2003; Chien et al, 2016).…”
Section: Resultsmentioning
confidence: 99%